1998
DOI: 10.1046/j.1525-1500.1998.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Suppression of Tumor Growth by Artepillin C Extracted from Brazilian Propolis

Abstract: Artepillin C was extracted from Brazilian propolis. Artepillin C (3,5-diprenyl-4-hydroxycinnamic acid) has a molecular weight of 300.40 and possesses antibacterial activity. When artepillin C was applied to human and murine malignant tumor cells in vitro and in vivo, artepillin C exhibited a cytotoxic effect and the growth of tumor cells was clearly inhibited. The artepillin C was found to cause significant damage to solid tumor and leukemic cells by the MTT assay, DNA synthesis assay, and morphological observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0
13

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 14 publications
6
126
0
13
Order By: Relevance
“…Clerodane diterpendoid shows a selective toxicity to tumor cells. A substance called Artepillin C has been isolated from propolis, and has been shown to have a cytotoxic effect on human gastric carcinoma cells, human lung cancer cells and mouse colon carcinoma cells in vitro (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clerodane diterpendoid shows a selective toxicity to tumor cells. A substance called Artepillin C has been isolated from propolis, and has been shown to have a cytotoxic effect on human gastric carcinoma cells, human lung cancer cells and mouse colon carcinoma cells in vitro (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…300 BC (3). Recently, numerous biological properties of propolis have been reported including cytotoxic, antiherpes, antitumor, free radical scavenging, antimicrobial, and anti-HIV activities (4)(5)(6)(7)(8)(9)(10). Because of the wide range of biological activities, recently propolis has been extensively used in food and beverages to improve health and prevent diseases (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason the com po sition of tropical propolis is quite different form propolis from temperate regions. Recently, tropi cal propolis has become a subject of increasing in terest for chemists and biologists (Banskota et Kimoto et al, 1998). In this paper we report the isolation and characterization of two new chalcones from propolis originating from El Salvador, Central Am erica, and their biological activity.…”
Section: Introductionmentioning
confidence: 88%
“…One finding indicated that DHCA exhibited inhibitory effects on renal carcinogenesis as a result of its oxy-radical scavenging property (Kimoto et al, 2000). Matsuno et al (1997) reported that DHCA was one of the effective anti-tumor compounds found in propolis and Kimoto et al (2001) and Kimoto et al (1998) showed that the DHCA is capable of reducing the mass of the tumor. Bohlmann and Jakupovic (1979) were the first to identify DHCA, which exists exclusively in Brazilian propolis (Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%